2005
DOI: 10.1093/ps/84.4.649
|View full text |Cite
|
Sign up to set email alerts
|

Novel preharvest strategies involving the use of experimental chlorate preparations and nitro-based compounds to prevent colonization of food-producing animals by foodborne pathogens

Abstract: Foodborne diseases caused by enterohemorrhagic Escherichia coli, Salmonella, and Campylobacter species are of public health and economic significance. Shedding of these pathogens during production and slaughter are risks for contamination of products for human consumption. Consequently, strategies are sought to prevent or reduce the carriage of these pathogens in food animals before slaughter. Experimental products containing chlorate salts have been proven efficacious in reducing concentrations of E. coli and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
1
18
0
2
Order By: Relevance
“…In 2006, European Community regulation 853/2004 permitted the use of substances other than water for decontamination of meat surfaces (3). Both physical and chemical reduction strategies, including treatment with steam, UV light, high hydrostatic pressure, essential oil fractions, acid, and sodium hypochlorite, have been investigated for their Campylobacter reduction potential, with various outcomes (1,9,10,13,16,24,28,33,35). DNA from dead bacterial cells has been shown to persist for up to 3 weeks following cell death (20), and it has also been demonstrated that the presence of DNA from dead Campylobacter cells can lead to an overestimation of the number of viable cells and, in some instances, even to false-positive results (45).…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, European Community regulation 853/2004 permitted the use of substances other than water for decontamination of meat surfaces (3). Both physical and chemical reduction strategies, including treatment with steam, UV light, high hydrostatic pressure, essential oil fractions, acid, and sodium hypochlorite, have been investigated for their Campylobacter reduction potential, with various outcomes (1,9,10,13,16,24,28,33,35). DNA from dead bacterial cells has been shown to persist for up to 3 weeks following cell death (20), and it has also been demonstrated that the presence of DNA from dead Campylobacter cells can lead to an overestimation of the number of viable cells and, in some instances, even to false-positive results (45).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there has been more interest in alternative chemicals and biologicals that can accomplish the same outcome without the potential for transmissible resistance. Recently, Anderson et al (2005) summarized their research on chlorate and nitro-based feed supplements demonstrating that they could reduce experimental infections of several foodborne pathogens in swine, cattle, sheep, and chickens. Bacteriocins which originate from bacteria and elicit antimicrobial properties against other bacteria have been examined for use in foods (Joerger, 2003).…”
Section: Feed Additives To Eliminate Colonized Salmonella Sppmentioning
confidence: 99%
“…Estratégias para prevenir ou reduzir a incidência de bactérias patogênicas na carne de bovinos têm sido pesquisadas para promover maior segurança alimentar e eficiência dos rebanhos (Callaway et al 2002, Anderson et al 2005. Essas bactérias estão presentes naturalmente no intestino de humanos e de animais e amplamente distribuídos no ambiente (Stevens 2002).…”
Section: Introductionunclassified
“…Escherichia coli e Salmonella sp. são agentes relevantes na saúde pública, ocasionam diarreia e mastite aos bovinos, promovendo perdas econômicas na pecuária (Anderson 2005, Duse et al 2015. Espécies de Enterobacteriaceae podem frequentemente serem encontradas no ecossistema ruminal (Scot et al 2008, Freitas et.…”
Section: Introductionunclassified